ISOLATION OF L LYXOFLAVINE FROM THE HUMAN MYOCARDIUM - SODI PALLARES, ERNESTO; MARTINEZ GARZA, HECTOR (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1978)
In a dog's hind leg with femoral artery ligated, peripheral circulation is immediately re-established, being subordinate to the main circulation but with a certain degree of independence The ligated leg disposes of sufficient amts of blood to re-establi
ARCH BIOCHEM
Keywords: ISOLATION, LYXOFLAVINE, HUMAN, MYOCARDIUM; CIENCIAS MEDICAS; CIENCIAS CLINICAS; MICROBIOLOGIA CLINICA